Bone Marrow Regeneration Promoted by Biophysically Sorted Osteoprogenitors From Mesenchymal Stromal Cells. (19th November 2014) - Poon, Zhiyong; Lee, Wong Cheng; Guan, Guofeng; Nyan, Lin Myint; Lim, Chwee Teck; Han, Jongyoon; Van Vliet, Krystyn J.
Abstract : This study used a high-throughput, biophysical, and label-free microfluidic sorting approach to isolate osteoprogenitor mesenchymal stromal cells (MSCs) from the culture-expanded bone marrow (BM)-derived MSC population. The results show that osteoprogenitor MSCs are potent cell factories that can mediate rapid regeneration of myeloablated BM, which fosters an environment conducive to hematopoietic recovery. This inertial microfluidic-based approach represents a significant advantage over current antibody- or fluorescence-based strategies to identify and select for MSC subpopulations. Abstract: Human tissue repair deficiencies can be supplemented through strategies to isolate, expand in vitro, and reimplant regenerative cells that supplant damaged cells or stimulate endogenous repair mechanisms. Bone marrow-derived mesenchymal stromal cells (MSCs), a subset of which is described as mesenchymal stem cells, are leading candidates for cell-mediated bone repair and wound healing, with hundreds of ongoing clinical trials worldwide. An outstanding key challenge for successful clinical translation of MSCs is the capacity to produce large quantities of cells in vitro with uniform and relevant therapeutic properties. By leveraging biophysical traits of MSC subpopulations and label-free microfluidic cell sorting, we hypothesized and experimentally verified that MSCs of large diameter within expanded MSC cultures were osteoprogenitors that exhibited significantly greater efficacy over other MSC subpopulations in bone marrow repair. Systemic administration of osteoprogenitor MSCs significantly improved survival rates (>80%) as compared with other MSC subpopulations (0%) for preclinical murine bone marrow injury models. Osteoprogenitor MSCs also exerted potent therapeutic effects as "cell factories" that secreted high levels of regenerative factors such as interleukin-6 (IL-6), interleukin-8 (IL-8), vascular endothelial growth factor A, bone morphogenetic protein 2, epidermal growth factor, fibroblast growth factor 1, and angiopoietin-1; this resulted in increased cell proliferation, vessel formation, and reduced apoptosis in bone marrow. This MSC subpopulation mediated rescue of damaged marrow tissue via restoration of the hematopoiesis-supporting stroma, as well as subsequent hematopoiesis. Together, the capabilities described herein for label-freeisolation of regenerative osteoprogenitor MSCs can markedly improve the efficacy of MSC-based therapies.